Synergistic PIM kinase and proteasome inhibition as a therapeutic strategy for MYC-overexpressing triple-negative breast cancer. Issue 3 (17th March 2022) - Kunder, Ratika; Velyunskiy, Michelle; Dunne, Sara F.; Cho, Byoung-Kyu; Kanojia, Deepak; Begg, Lauren; Orriols, Adrienne M.; Fleming-Trujillo, Erica; Vadlamani, Pranathi; Vialichka, Alesia; Bolin, Rosemary; Perrino, Jessica N.; et al.
Summary: Triple-negative breast cancer (TNBC) is the breast cancer subtype with the poorest clinical outcome. The PIM family of kinases has emerged as a factor that is both overexpressed in TNBC and associated with poor outcomes. Preclinical data suggest that TNBC with an elevated MYC expression is sensitive to PIM inhibition. However, clinical observations indicate that the efficacy of PIM inhibitors as single agents may be limited, suggesting the need for combination therapies. Our screening effort identifies PIM and the 20S proteasome inhibition as the most synergistic combination. PIM inhibitors, when combined with proteasome inhibitors, induce significant antitumor effects, including abnormal accumulation of poly-ubiquitinated proteins, increased proteotoxic stress, and the inability of NRF1 to counter loss in proteasome activity. Thus, the identified combination could represent a rational combination therapy against MYC-overexpressing TNBC that is readily translatable to clinical investigations. Graphical abstract: Highlights: Combining PIM kinase and proteasome inhibitors induces synergies in high-MYC TNBC PIM inhibition-induced ROS level elevation alone might be well tolerated in TNBC cells Both NRF1 and MYC can contribute to maintaining proteasome activity The mechanisms of drug synergy involve increased proteotoxic stress Abstract : Kunder et al. identify a drug combination that targets PIM kinases and the proteasome as a potentially clinically viable tool to induce significant cytotoxicity in high-MYC TNBC cells. The findings encourage the proposed combination therapy to be further evaluated in other high-MYC cancer types that express PIM kinases.